2006
DOI: 10.1111/j.1365-2915.2006.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

First description of the endogenous life cycle of Hypoderma sinense affecting yaks and cattle in China

Abstract: Larvae belonging to five species of Hypoderma spp. (Diptera, Oestridae) cause myiasis in wild and domestic ruminants that is characterized by migrations within deep tissues. In China hypodermosis is one of the most important arthropod diseases affecting ruminants and, moreover, represents a significant zoonosis, with numerous reports of Hypoderma spp. affecting farmers. Recently, a sixth species, Hypoderma sinense Pleske, has been rediscovered but the endogenous migration pathway within the host body is comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…It has been reported that the 1st instar larvae of H. lineatum and H. sinense parasitized in the esophagus and those of H. bovis in the epidural fat of the spinal canal [2, 4, 15, 21]. However, as observed in our previous study [13], a large proportion of 1st instar larvae were found not only in the esophagus but also in the rumen.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…It has been reported that the 1st instar larvae of H. lineatum and H. sinense parasitized in the esophagus and those of H. bovis in the epidural fat of the spinal canal [2, 4, 15, 21]. However, as observed in our previous study [13], a large proportion of 1st instar larvae were found not only in the esophagus but also in the rumen.…”
Section: Discussionsupporting
confidence: 51%
“…Unfortunately, species identification was not conducted in this study. Although morphological identification for the species of 1st instar larvae is impossible [15], DNA identification of species would help to understand the migration patterns of H. bovis, H. lineatum and H. sinense in yaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An awareness of the risk for parasitism of F1 yak × beef hybrids by horn flies is important for practising veterinarians, entomologists and agricultural producers in Europe and North America in order that appropriate monitoring protocols and preventative treatment strategies can be developed, and decisions on interventions made during peak parasitism periods (Oyarzún et al, 2008;Swiger & Payne, 2016). Initial assessments such as that reported in this study, like the initial reports by Otranto et al (2006) for Hypoderma species (Diptera: Oestridae) in yaks and cattle in China, have similar medical and veterinary applications that are also relevant to the traditional regions of production of yaks and their associated hybrids in Asia (Saravanan et al, 2008;Barsila et al, 2014;Angell et al, 2018).…”
Section: Discussionmentioning
confidence: 84%